ANALISYS OF ECONOMIC VIABILIT FOR A MINIMUM PROCESSED VEGETABLE AGROINDUSTRY - Gardini, Ulisses Rogério; Souza, Rafael Antonio de; Lorando, Tatiane Roberta dos Santos Pires; Pandolfi, Marcos Alberto Claudio (Revista Interface Tecnológica, 2020)
With today’s busy life, people have had less and less time to devote to preparing their food, preferring practical and healthy foods for consumption. The Minimally Processed food sector is still very little explored in Brazil, with significant growth potential, as it is a product with greater added value and with 100% utilization, since the consumer uses everything he buys, because at the time of purchase, the product has already undergone selection. The search for consumers by this market trend was what led us to research on the topic, in order to seize the opportunity and diagnose the economic feasibility of setting up a Minimally Processed Vegetables and Vegetables agribusiness. We focus our research on lettuce, cabbage, carrot and beet products, with 5% of production turned to organic products, also seeking to reach this market niche. Market research was carried out, as well as financial analysis and through various tools such as NPV (Net Present Value), IRR (Internal Rate of Return) and Payback, we found that the project proved to be viable for investment.